Clinicopathological features and risk factors for local recurrence of breast phyllodes tumors: a dual-center, 12-year, retrospective study - Li, Yiwen; Chen, Heyan; Qu, Fengjiang; Qu, Xiaoying; Zhang, Qihe; Feng, Kexuan; Li, Xiaoduo; Zhang, Huimin; Fan, Zhimin (Frontiers in Oncology, 2025)
PurposeTo clarify the risk factors of phyllodes tumor (PT) for local recurrence (LR).MethodsData from 829 patients with pathologically confirmed benign, borderline and malignant PT of the breast, diagnosed from between 2011 to 2023, were retrieved from the electronic databases of the First Hospital of Jilin University and the First Affiliated Hospital of Xi’an Jiaotong University. Kaplan-Meier curves and Cox proportional-hazards model were conducted to determine the independent risk factors for LR in each group.ResultsOf 829 PT patients, 634 (76.5%), 142 (17.1%), and 53 (6.4%) were diagnosed with benign, borderline, and malignant PT, respectively. The LR rates were 5.4%, 9.9%, 13.2%, respectively. The median patient age was 38 years and the median follow-up time was 2.8 (range, 0.2-12.1 years). Of these patients, 13 (2.1%) were diagnosed with benign bilateral PT. Multivariate analysis identified bilateral involvement as a risk factor for LR of benign PT (p=0.010). Also, univariate analysis identified young age (≤35 years, p=0.046) as an independent risk factors for LR of borderline PT. Of the patients with malignant PT, univariate analysis found that breast-conserving surgery (BCS) (p=0.008) were associated with an increased risk for LR of malignant PT.ConclusionsBilateral PT was a risk factor for LR of benign PT, young age (≤35 years) was associated with poor prognosis of borderline PT, BCS were high risk factors for LR of malignant PT. This study identifies LR risk factors based on tumor grading, which contributes to individualized clinical risk assessment. Future research could further explore how to incorporate these factors into clinical decision-making models for PT and other soft tissue tumors.